2020
DOI: 10.1111/ejn.14674
|View full text |Cite
|
Sign up to set email alerts
|

The basic helix‐loop‐helix transcription factor TCF4 impacts brain architecture as well as neuronal morphology and differentiation

Abstract: Germline mutations in the basic helix‐loop‐helix transcription factor 4 (TCF4) cause the Pitt–Hopkins syndrome (PTHS), a developmental disorder with severe intellectual disability. Here, we report findings from a new mouse model with a central nervous system‐specific truncation of Tcf4 leading to severe phenotypic abnormalities. Furthermore, it allows the study of a complete TCF4 knockout in adult mice, circumventing early postnatal lethality of previously published mouse models. Our data suggest that a TCF4 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 72 publications
(112 reference statements)
0
24
0
Order By: Relevance
“…The factor TCF4 present in the network of N'Dama, belongs to a basic helix-loop-helix family which plays an integral role in Wnt signalling and neuronal differentiation especially in the brain development [146][147][148][149][150]. Furthermore, TCF4 is also involved in the immune responses through the production of plasmacytoid Dendritic Cells (pDCs), which respond to viral nucleic acids and autoimmune diseases, by the secretion of cytokines such as type I interferons [151][152][153][154].…”
Section: Cooperative Tfs In Lymph Node Tissuementioning
confidence: 99%
“…The factor TCF4 present in the network of N'Dama, belongs to a basic helix-loop-helix family which plays an integral role in Wnt signalling and neuronal differentiation especially in the brain development [146][147][148][149][150]. Furthermore, TCF4 is also involved in the immune responses through the production of plasmacytoid Dendritic Cells (pDCs), which respond to viral nucleic acids and autoimmune diseases, by the secretion of cytokines such as type I interferons [151][152][153][154].…”
Section: Cooperative Tfs In Lymph Node Tissuementioning
confidence: 99%
“…Adult-born neuron survival is highly dependent on maturation and synaptic integration (38)(39)(40). Recent studies reported that loss-of-Tcf4 causes delayed maturation of embryonically and early postnatally born neurons, impairs dendrite and synapse formation in the developing cortex (17,41), and decreases spine density of mature cortical and hippocampal neurons (42). When analysing the marker pro le of 4-week old adult-born neurons, we found that neurons in Tcf4Het mice less frequently displayed a mature marker pro le, which suggests the possibility that Tcf4 haploinsu ciency impaired maturation and thereby decreased survival of adult-born neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, TCF4 controls proliferation of cortical precursor cells, balances precursor proliferation versus differentiation, regulates fate choices and migration, and modulates dendrite and spine development (14)(15)(16)(17)(18). Loss of Tcf4 causes imbalanced generation of deep vs. upper layer neurons, delays neuronal differentiation, and impairs dendritogenesis and synapse formation (14,17,19). Development of the hippocampal formation appears to be particularly reliant on precise TCF4 dosage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents, TCF4 controls proliferation of cortical precursor cells, balances precursor proliferation versus differentiation, regulates fate choices and migration, and modulates dendrite and spine development (14)(15)(16)(17)(18). Loss of Tcf4 causes imbalanced generation of deep vs. upper layer neurons, delays neuronal differentiation, and impairs dendritogenesis and synapse formation (14,17,19). Development of the hippocampal formation appears to be particularly reliant on precise TCF4 dosage.…”
Section: Introductionmentioning
confidence: 99%